The role of a nurse in the implementation of cardiovascular disease screening program - Petraškevič, Božena; Greičienė, Svetlana (Slauga. Mokslas ir praktika, 2020)
Cardiovascular diseases (CVD) the most common death cause among Lithuanians. According to World Health Organization (WHO) calculations, each year 17 million people all over the world die of CVD, 4.35 million people in European countries. In primary healthcare institutions, general practitioners are the ones to provide information on CVD screening programs (SP). What is more, A. Eigirdaite, states that in most cases, the physician has a major impact on the patient’s decision when selecting the screening program. The role of a nurse in the implementation of CVD SP, on the other hand, has not been thoroughly analyzed yet.The aim of the thesis: To analyze the role of a nurse in the implementation of cardiovascular diseases screening program.Study objectives: to examine the nurses’ attitude towards the implementation of cardiovascular diseases screening program.; to analyse the role of a nurse in the implementation of cardiovascular diseases screening program.Methodology. A quantitative descriptive study was carried out using the questionnaire method. The study was conducted from October till December of year 2016 and it involved 44 participants (nurses).Results. Two-thirds of nurses stated their role in implementing the CVD SP to be significant. According to twothirds of the respondents, the benefits of the program and the sense of duty are the two most motivating factors that make nurses encourage patients participation in CVD SP. Most nurses believe that an excessive workload is the main issue preventing a successful implementation of CVD SP. Nurses perform a wide variety of procedures during the implementation of CVD SP: informing patients about the CVD aims and measures, providing information notices of the ongoing CVD, informing patients about upcoming blood tests, directing patients to a laboratory for blood tests, measuring height and weight as well as waist circumference, evaluating the BMI, measuring blood pressure and heart rate (HR), recording electrocardiogram (ECG) and booking physician appointments.
Keywords: nurses's functions; primary healthcare; screening program